2023
DOI: 10.3390/jpm13040673
|View full text |Cite
|
Sign up to set email alerts
|

Familial CCM Genes Might Not Be Main Drivers for Pathogenesis of Sporadic CCMs-Genetic Similarity between Cancers and Vascular Malformations

Abstract: Cerebral cavernous malformations (CCMs) are abnormally dilated intracranial capillaries that form cerebrovascular lesions with a high risk of hemorrhagic stroke. Recently, several somatic “activating” gain-of-function (GOF) point mutations in PIK3CA (phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit p110α) were discovered as a dominant mutation in the lesions of sporadic forms of cerebral cavernous malformation (sCCM), raising the possibility that CCMs, like other types of vascular malformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 227 publications
0
10
0
1
Order By: Relevance
“…In familiar cases, CCM germline mutations occur earlier than somatic PIK3CA mutations, nevertheless, CCM mutations may be a secondary event following the mutation of PI3K pathway genes in sporadic cases. [3][4][5] Two subgroups' lesions harboured different genotypes and related phenotypes, which implies an underlying molecular mechanism within them. Recent studies indicated that PIK3CA mutation was associated with haemorrhagic events in CCMs.…”
Section: Genotype-phenotype Correlations In Multiple Lesions Of Famil...mentioning
confidence: 99%
See 1 more Smart Citation
“…In familiar cases, CCM germline mutations occur earlier than somatic PIK3CA mutations, nevertheless, CCM mutations may be a secondary event following the mutation of PI3K pathway genes in sporadic cases. [3][4][5] Two subgroups' lesions harboured different genotypes and related phenotypes, which implies an underlying molecular mechanism within them. Recent studies indicated that PIK3CA mutation was associated with haemorrhagic events in CCMs.…”
Section: Genotype-phenotype Correlations In Multiple Lesions Of Famil...mentioning
confidence: 99%
“…Jie Wang 1,2 Jihong Tang 3,4 Yingxi Yang 4 Yuming Jiao 1,2 Ran Huo 1,2 Hongyuan Xu 1,2 Shaozhi Zhao 1,2 Yingfan Sun 1,2 Qiheng He 1,2 Qifeng Yu 1,2 Shuo Wang 1,2 Jizong Zhao 1,2 Jiguang Wang 3,4,5 Yong Cao…”
Section: A U T H O R C O N T R I B U T I O N Sunclassified
“…Although further research and validation is needed, plasma water T 2 shows potential for addressing that need. 1 F, female; M, male 2 H, Hispanic; NH, non-Hispanic 3 median (interquartile range), full range 4 individuals carrying the same Baca familial CCM1 hemizygous mutation 5 individuals with no known CCM mutation and poor cardiometabolic health (T 2 ≤700.1 msec) 6 individuals with no known CCM mutation and good cardiometabolic health (T 2 >700.1 msec) 7 individuals with no known CCM mutation; combination of unhealthy and healthy groups…”
Section: Strengths and Significancementioning
confidence: 99%
“…CCMs are characterized by two distinct features, each associated with both common and unique causative genetic mutation landscapes. These features encompass familial CCMs (fCCMs), which are inherited, and sporadic CCMs (sCCMs), which arise de novo [2,4,5]. The focus of this study is on a single "common Hispanic" fCCM1 mutation due to its inheritable nature and traceable genetic lineage route.…”
Section: Introductionmentioning
confidence: 99%
“…CCMs are characterized by two distinct features, each associated with both common and unique causative genetic mutation landscapes. These features encompass familial CCMs (fCCMs), which are inherited, and sporadic CCMs (sCCMs), which arise de novo (Zhang 2011 ;Zhang et al 2022; Zhang et al 2023). The focus of this study is on a single "common Hispanic" fCCM1 mutation due to its inheritable nature and traceable genetic lineage route.…”
Section: Introductionmentioning
confidence: 99%